COMPARATIVE ANALYSIS OF TRANSPORT MANAGEMENT PREPAREDNESS - EVIDENCE FROM CEE COUNTRIES - Aćimović, Slobodan; Mijušković, Veljko; Fedajev, Aleksandra (Industrija, 2023)
Being the most cost-dominant component of the logistics management system, transport plays a vital role in the realization of trade activities across Europe, both on a national and micro level. Various indicators determine the efficiency of the realization of transport activities, amongst which the following hold high importance: quality of transport infrastructure (air, road, maritime, etc.), transport safety and security elements, as well as export/import procedures, etc. This paper aims to perform a comparative analysis among chosen European countries (focusing on CEE countries) concerning the level of transport management preparedness based on the previously mentioned elements. The analysis is performed by using the PROMETHEE II and entropy method. The obtained results should help determine the differences and similarities in transport management preparedness to synchronize better future national policies, strategies, and procedures concerning this issue.